The Exclusionary Data Conduct in Digital Mergers: An Indonesian Competition Law Perspective - Kukuh Tejomurti; Ashyah Azzahra (JUSTISI, 2026)
The aim of this study is to examine the regulatory gap in Indonesian competition law regarding the use of user data by platform-based companies after a digital merger, by examining how the current legal framework responds to data-based exclusive practices and assessing its adequacy in regulating the dynamics of digital merger control. The method of this study examines the norms, principles, and legal doctrines contained in legislation, court decisions, legal theory, and scientific writings related to competition law, which are analyzed using current theories of harm. The novelty of this research is the application of the Newer Theory of Harm in analyzing digital mergers and acquisitions, particularly in privacy-based theory, where consumer data protection is an important aspect that needs to be considered in mergers and acquisitions. Consumer data privacy protection can be used as a quality assessment that must be met in the testing process that must be carried out before mergers and acquisitions. The results of the study show that merger regulations in Indonesian competition law are still oriented towards market concentration and price impacts, so they are not yet fully capable of addressing data-based exclusive practices and digital ecosystem dominance post-merger. This study concludes that digital merger supervision in Indonesia needs to be developed by expanding the analysis of big data control and its implications for fair business competition, taking lessons from the experience of the German Competition Authority and the European Union's Digital Markets Act regulations. The conclusion of this study concerns the assessment of mergers and acquisitions in Indonesian Competition Law; learning from the German Competition Authority and the European Union's Digital Markets Act, the government must expand its analysis of how access to big data affects a healthy competition ecosystem.